Accuracy and Reproducibility of a Modified Echocardiographic Method for Right Ventricular Output Calculation in Neonates - Carlotta Milocchi; Silvia Nogara; Giorgia Mazzuca; Federica Runfola; Martina Ciarcià; Iuri Corsini; Benjamim Ficial (Journal of Cardiovascular Development and Disease)
We aimed to evaluate the accuracy and reproducibility of right ventricular output (RVO) using different anatomical landmarks: the internal pulmonary valve diameter (PVD) between the valve hinge points (hinge-PVD) according to the traditional technique, and PVD between the valve leaflet tips (tip-PVD). This was a retrospective analysis of prospective collected data. All neonates with echocardiographic measurements of RVO and left ventricular output (LVO) without congenital heart disease, including patent ductus arteriosus and patent foramen ovale > 3 mm, were included. Accuracy was assessed by comparison with LVO. Intra- and inter-observer reproducibility of the off-line analysis were assessed. Forty-five neonates were included. RVO calculation with tip-PVD was more accurate than hinge-PVD in comparison with LVO, r2 0.712 versus 0.464, bias (95% limits of agreement) 1.4 mL/kg/min (−26–29 mL/kg/min) versus 61 mL/kg/min (−11–132 mL/kg/min), respectively. Both hinge-PVD and tip-PVD presented similar reproducibility, with an intra-observer bias (95% LOA) of 0.3 (−1.0–0.5) and –0.2 (−0.8–0.5) respectively, and an inter-observer bias of 0.1 (−1.3–1.6) and 0.1 (−1.4–1.6). RVO calculation using tip-PVD was more accurate than the conventional technique, with similar reproducibility.